Fecal metabolomics reveals products of dysregulated proteolysis and altered microbial metabolism in obesity-related osteoarthritis. Issue 1 (January 2022) - Rushing, B.R.; McRitchie, S.; Arbeeva, L.; Nelson, A.E.; Azcarate-Peril, M.A.; Li, Y.-Y.; Qian, Y.; Pathmasiri, W.; Sumner, S.C.J.; Loeser, R.F.
Summary: Objective: The objective of this exploratory study was to determine if perturbations in gut microbial composition and the gut metabolome could be linked to individuals with obesity and osteoarthritis (OA). Methods: Fecal samples were collected from obese individuals diagnosed with radiographic hand plus knee OA ( n  = 59), defined as involvement of at least 3 joints across both hands, and a Kellgren–Lawrence (KL) grade 2–4 (or total knee replacement) in at least one knee. Controls ( n  = 33) were without hand OA and with KL grade 0–1 knees. Fecal metabolomes were analyzed by a UHPLC/Q Exactive HFx mass spectrometer. Microbiome composition was determined in fecal samples by 16 S ribosomal RNA amplicon sequencing (rRNA-seq). Stepwise logistic regression models were built to determine microbiome and/or metabolic characteristics of OA. Results: Untargeted metabolomics analysis indicated that OA cases had significantly higher levels of di- and tripeptides and significant perturbations in microbial metabolites including propionic acid, indoles, and other tryptophan metabolites. Pathway analysis revealed several significantly perturbed pathways associated with OA including leukotriene metabolism, amino acid metabolism and fatty acid utilization. Logistic regression models selected metabolites associated with the gut microbiota and leaky gut syndrome as significant predictors of OA status, particularly when combined with the rRNA-seq data. Conclusions: Adults with obesity and knee plus hand OA have distinct fecal metabolomes characterized by increased products of proteolysis, perturbations in leukotriene metabolism, and changes in microbial metabolites compared with controls. These metabolic perturbations indicate a possible role of dysregulated proteolysis in OA.